EVALUASI PEMANFAATAN LABORATORIUM DALAM MENINGKATKAN KOMPETENSI TATA KECANTIKAN KULIT MAHASISWA PRODI TATA RIAS UNIVERSITAS NEGERI MEDAN - Tarigan, Christine Ulina; Budiastuti, Emy (Universitas Negeri Yogyakarta, 2020)
The purpose of this study was to determine the extent of laboratory utilization from the standpoint of planning, implementation, and evaluation which used CIPP (context, input, process, product) model in the management of the Beauty Education Study Program at State University of Medan. Research model using qualitative approach to evaluation the facilities and infrastructure, utilization, and the involvement of students, head of laboratory, laboratory assistants, and lecturers of facial care courses with facial electric technology which influence the student's practical competency with data collected by interviews and documentation on 60 students of third semester in the practical of facial electric treatment courses because it had homogeneous characteristics and capabilities. Data analysis techniques used is descriptive analysis and the results of this study indicate that the tendency of laboratory utilization 31.67% are sufficient, laboratory facilities and infrastructure 33.33% are sufficient, laboratory utilization in practical implementation 33.33% are sufficient, the competence of students 33.33% are less. There is a positive relationship between the variable's utilization of laboratory, laboratory facilities and infrastructure and the practical implementation of the students' competencies generated by the value of Î± = 0.00. It means the availability of facilities and adequate practical implementation can improve cognitive, psychomotor and affective competencies of student.